The Role of Nodes Distribution in Extending the Lifetime of Wireless Sensor Networks - Mitra Javadzadeh; Aliazam Abbasfar (International Journal of Distributed Sensor Networks)
One of the most important issues in sensor networks is prolonging the network lifetime. In this paper, we demonstrate that given a constant number of nodes, how distribution of nodes affects the lifetime. For this purpose, we first show that in a network with cluster-based routing protocol, nodes do not have equal importance, and their importance depends on their location, and we determine the most critical regions. We prove that the uniform distribution of nodes is not a good distribution. Finally, we propose a solution for the best distribution that concentrates the population of nodes on critical areas. Simulation results of our proposed distribution show a remarkable increase in network lifetime.